2002
DOI: 10.1093/annonc/mdf020
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative inhibitory effect of ZD1839 (Iressa) in combination with trastuzumab (Herceptin) on human breast cancer cell growth

Abstract: These data suggest that combined treatment with drugs that target EGFR and ErbB-2 might result in an efficient inhibition of tumor growth in those breast carcinoma patients whose tumors co-express both receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
147
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(156 citation statements)
references
References 29 publications
7
147
0
2
Order By: Relevance
“…In agreement with these findings, co-expression of EGFR, ErbB-2 and ErbB-3 was also found to have a negative synergistic effect on patient outcome, independent of tumor size or lymph node status [9]. Different anti-EGFR agents, including the EGFR tyrosine kinase inhibitor (EGFR-TKI) gefitinib (ZD1839, Iressa), have shown to inhibit the growth of human breast carcinoma cells [10][11][12][13][14]. We and other research groups have demonstrated that breast cancer cell lines with high levels of expression of ErbB-2 are more sensitive to gefitinib as compared with ErbB-2-negative cells [11][12][13][14].…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…In agreement with these findings, co-expression of EGFR, ErbB-2 and ErbB-3 was also found to have a negative synergistic effect on patient outcome, independent of tumor size or lymph node status [9]. Different anti-EGFR agents, including the EGFR tyrosine kinase inhibitor (EGFR-TKI) gefitinib (ZD1839, Iressa), have shown to inhibit the growth of human breast carcinoma cells [10][11][12][13][14]. We and other research groups have demonstrated that breast cancer cell lines with high levels of expression of ErbB-2 are more sensitive to gefitinib as compared with ErbB-2-negative cells [11][12][13][14].…”
Section: Introductionmentioning
confidence: 63%
“…We and other groups have previously demonstrated that a synergistic anti-tumor effect occurs when breast cancer cells that co-express EGFR and ErbB-2 are treated with a combination of gefitinib and the anti-ErbB-2 monoclonal antibody trastuzumab [11][12][13]. In particular, we demonstrated that the two drugs have a strong synergism in breast cancer cells by using a wide range of concentrations of both drugs and isobolographic analysis [13].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations